Confessions of a Conjuror - Brown, Derren (London Channel 4 Books, 2010)
The inside of Derren Brown's head is a strange and mysterious place. Now you can climb inside and wander around. Find out just how Derren's mind works, see what motivates him and discover what made him the weird and wonderful person he is today. Obsessed with magic and illusions since childhood, Derren's life to date has been an extraordinary journey and here, in "Confessions of a Conjuror," he allows us all to join him on a magical mystery tour - to the centre of his brain...Taking as his starting point the various stages of a conjuring trick he's performing in a crowded restaurant, Derren's endlessly engaging narrative wanders through subjects from all points of the compass, from the history of magic and the fundamentals of psychology to the joys of internet shopping and the proper use of Parmesan cheese. Brilliant, hilarious and entirely unlike anything else you have ever read before, "Confessions of a Conjuror" is also a complete and utter joy.
English Biography.
Keywords: Magicians -- Great Britain -- Brown, Derren